A Prospective Observation Study of Medical Toxicology Consultation in a U.S. Combat Theater. Issue 11 (1st November 2016) - Maddry, Joseph K.; Ng, Patrick C.; Sessions, Daniel; Bebarta, Vikhyat S.
ABSTRACT: Objectives: Since 2001, U.S. military personnel and active duty, uniformed physicians providing medical support have been deployed to Afghanistan. Medical toxicologists are among the physicians deployed. There is a paucity of information present in the literature that has documented cases treated by toxicologists in theater. This prospective observational study describes 15 male patients treated in theater by a military medical toxicologist. Methods: We performed a prospective observational study in which a medical toxicologist consulted and reported on deployed toxicology cases occurring during a 5-month deployment to Bagram, Afghanistan. Results: Fifteen toxicology cases were collected during the 5-month period. The patients included three Afghan civilians, three U.S. civilians, and nine U.S. military personnel. Eight cases were attempts at recreational euphoria, two were self-harm attempts, two were from performance-enhancing supplements, two were accidental occupational exposures and one was alcohol withdrawal. Methanol was the most common exposure followed by dextromethorphan, supplements, opiates, and chlorine gas. Conclusion: In our study, we found that toxic alcohols and nonprescription medications were the most common exposures. In addition, this is the first study to describe bedside toxicology consults for U.S. combat forces in theater and the use of an observation unit for critically ill patients.